2015
DOI: 10.1371/journal.pntd.0004282
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Paracoccidioides Hypoxia Response Reveals New Insights into Pathogenesis Mechanisms of This Important Human Pathogenic Fungus

Abstract: BackgroundHypoxic microenvironments are generated during fungal infection. It has been described that to survive in the human host, fungi must also tolerate and overcome in vivo microenvironmental stress conditions including low oxygen tension; however nothing is known how Paracoccidioides species respond to hypoxia. The genus Paracoccidioides comprises human thermal dimorphic fungi and are causative agents of paracoccidioidomycosis (PCM), an important mycosis in Latin America.Methodology/Principal FindingsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 101 publications
4
43
0
Order By: Relevance
“…An evaluation of mitochondrial activity showed a lower activity at the first 12 hours under hypoxia, and restoration of activity at 24 hours, in agreement with the proteomic results, showing the potential for adaptation of this fungus under low oxygen levels [162]. The same work revealed that P. lutzii contains homologs of SrbA, a sterol regulatory element binding protein (SREBP) and key regulator of hypoxia adaptation in fungi [162]. Functional complementation of an Aspergillus fumigatus srbA null mutant by the Paracoccidioides srbA ( PbsrbA ) gene restored the null mutant hyphal growth under hypoxia, which suggests that PbsrbA may promote adaptation to hypoxic microenvironments.…”
Section: Defenses To Host Environment Stressorssupporting
confidence: 79%
“…An evaluation of mitochondrial activity showed a lower activity at the first 12 hours under hypoxia, and restoration of activity at 24 hours, in agreement with the proteomic results, showing the potential for adaptation of this fungus under low oxygen levels [162]. The same work revealed that P. lutzii contains homologs of SrbA, a sterol regulatory element binding protein (SREBP) and key regulator of hypoxia adaptation in fungi [162]. Functional complementation of an Aspergillus fumigatus srbA null mutant by the Paracoccidioides srbA ( PbsrbA ) gene restored the null mutant hyphal growth under hypoxia, which suggests that PbsrbA may promote adaptation to hypoxic microenvironments.…”
Section: Defenses To Host Environment Stressorssupporting
confidence: 79%
“…Yeasts Saccharomyces cerevisiae and Candida albicans have no apparent SREBP orthologues, whereas Schizosaccharomyces pombe and Cryptococcus neoformans contain functional SREBPs that regulate ergosterol biosynthesis and aid in adaptation to hypoxic conditions293031. Amongst the filamentous fungi, SrbA from A. fumigatus is the only characterised SREBP, except for SrbA from Paracoccidioides , the coding sequence of which was shown to function heterologously in A. fumigatus cells32. Bioinformatic analysis suggests that important plant pathogen species Fusarium and Magnaporthe may contain SREBPs, although the physiological functions of these proteins are yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The proteomic approach was performed using NanoUPLC‐MS E as previously described (Murad and Rech, ; Murad et al, ) and adapted for samples of Paracoccidioides species in our laboratory (Bailão et al, ; Lima et al, , ; Oliveira et al, ). The peptide and protein data were generated by the PLGS process and data from analysis are shown in Figure S6.…”
Section: Resultsmentioning
confidence: 99%